1991
DOI: 10.1002/j.1460-2075.1991.tb07727.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of dense core granules in wild type and mutant Tetrahymena thermophila.

Abstract: Tetrahymena thermophila, a ciliated protozoan, has a well‐developed pathway of regulated secretion from dense core granules called mucocysts. Since exocytosis‐defective mutants are available, steps in the biogenesis of dense core granules and their fusion with the plasma membrane may be resolved genetically. To describe the steps in biochemical terms, we have generated antisera against mucocyst content proteins. One antiserum is directed against a calcium binding protein, p40, that is released on stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
11

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 42 publications
2
67
0
11
Order By: Relevance
“…Grt1p was first detected as one of the most abundant DCG components released during exocytosis (32). Biochemical analysis showed that Grt1p differs in its solubility from the Grl proteins and also that it is packaged intact in DCGs rather than undergoing proteolytic processing (31).…”
mentioning
confidence: 99%
“…Grt1p was first detected as one of the most abundant DCG components released during exocytosis (32). Biochemical analysis showed that Grt1p differs in its solubility from the Grl proteins and also that it is packaged intact in DCGs rather than undergoing proteolytic processing (31).…”
mentioning
confidence: 99%
“…Cell Calcium (1998) 23 (5), [349][350][351][352][353][354][355][356][357][358][359][360] genetic analyses [55,56]. This is substantiated by our present finding of an abnormal set of trichynins in tnd1, undergoing only partial DTT-induced MW shift on SDS-PAGE, and greatly reduced Caz+-binding.…”
Section: Lack Of Contents' Decondensation In Tnd1 Cellsmentioning
confidence: 57%
“…Note that equal amounts of protein were applied to lanes in Figure 11. Imperfect cleavage can be only one reason of reduced 45Ca binding, since the 45 kDa band binds no [55,56].…”
Section: Experiments With Isolated Trichocysts Sds-page and 45ca Ovementioning
confidence: 99%
“…Similar mutants defective on different levels of the secretory pathway have been obtained from Tetrahymena (Sauer and Kelly, 1995;Melia et al, 1998). With these cells it was also possible to show that secretory content sorting precedes condensation into a mature form (Turkewitz et al, 1991;Bowman and Turkewitz, 2001).…”
Section: Ill Standard Route: Endoplasmic Reticulum To Golgi Complex mentioning
confidence: 99%